Irradiation as a novel approach to improve quality of Tropaeolum majus L. flowers: benefits in phenolic profiles and antioxidant activity - Koike, Amanda (2015)
Edible flowers are increasingly used in food preparations, requiring new approaches to improve their conservation and safety. Food irradiation, particularly electron beam and gamma irradiation, is legally recognized to extend shelf life, improve hygienic quality and disinfest foods. Garden nasturtium (Tropaeolum majus L.) flowers are widely used in food preparations, being also known for their antioxidant properties and high content of phenolics. The purpose of this study was to evaluate the dose-response effects of gamma and electron beam irradiation (unirradiated and doses of 0.5, 0.8 and 1 kGy) on its antioxidant activity and phenolic compounds. Kaempferol-O-hexoside-O-hexoside was the most abundant compound, while pelargonidin-3-O-sophoroside was the major anthocyanin. The flowers showed high antioxidant activity, in particular as reducing agents. The interaction among the effects of irradiation dose and irradiation technology was a significant source of variation for all parameters. In general, irradiated samples gave higher antioxidant activity, maybe due to their higher amounts of phenolic compounds. Anthocyanins were the sole compounds negatively affected by irradiation. These differences were reflected in the linear discriminant analysis, which allowed the perfect separation of the applied doses, as also both irradiation technologies. Accordingly, irradiation represents a feasible technology to preserve the quality of edible flowers.